2009
DOI: 10.1348/147608308x397059
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation: An interpretative phenomenological analysis of mental health professionals' experiences of empathy in clinical work with an interpreter

Abstract: The difficulties participants encountered in work with an interpreter highlight a need for training in cross-language empathy for interpreters and mental health professionals, and encourage the use of transcultural models of psychotherapy in work with non-English speaking service-users. Some of the difficulties associated with adopting traditional humanistic models of empathy, which tend to centralize the therapist within empathic processes, when working with interpreters are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 29 publications
3
44
3
Order By: Relevance
“…Although role demands may be made more manageable by depersonalizing the recipients of interpretation services (Maslach et al, 2001), a resulting lack of empathy may also lead to the loss of a compassionate voice for those rendered more vulnerable because of language and cultural differences and barriers (Pugh & Vetere, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although role demands may be made more manageable by depersonalizing the recipients of interpretation services (Maslach et al, 2001), a resulting lack of empathy may also lead to the loss of a compassionate voice for those rendered more vulnerable because of language and cultural differences and barriers (Pugh & Vetere, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although sadness and suffering may be diagnosed as a symptom of depression in western cultures, people from nonwestern cultures may view these emotions as an empowerment to their cultural identities rather than an illness condition [44,45]. A study found mental health providers hold paradoxical attitudes about interpreters' role, describing ''the interpreter as both an obstacle and a facilitator of the empathic process, helping them to develop, and at times inhibiting, a sense of empathic connectivity with the client'' [46]. The complexity of cross-cultural implications and clinical meanings of individuals' emotions has been a challenging issue for healthcare professionals [6].…”
Section: Interpreters' Management and Performance Of Others' Emotionsmentioning
confidence: 99%
“…A significant portion of the current literature emphasizes that therapeutic empathy be understood more ecologically, as a process that focuses not just on the person, but rather on the person-in-context/environment (Dyche and Zayas 2001;Freedberg 2007;Jenkins 1999;Martin and Dawda 1999;Nissim-Sabat 1995;O'Hara 1999;Parson 1993;Pedersen 2008;Pugh and Vetere 2009;Raines 1990;Sells et al 2004). This portion of the literature coincides with increased attention to therapist cultural competence (Sue and Lam 2002;Wintersteen et al 2005).…”
Section: Empathy and Contextmentioning
confidence: 99%